Cumulated time to chart closure: a novel electronic health record-derived metric associated with clinician burnout - Shah, Madhura; De Arrigunaga, Sofia; Forman, Leah S; West, Matthew; Rowe, Susannah G; Mishuris, Rebecca G (JAMIA open, 2024)
Objective We sought to determine whether average cumulated time to chart closure (CTCC), a novel construct to measure clinician workload burden, and electronic health record (EHR) measures were associated with a validated measure of burnout. Materials and methods Physicians at a large academic institution participated in a well-being survey that was linked to their EHR use data. CTCC was defined as the average time from the start of patient encounters to chart closure over a set of encounters. Established EHR use measures including daily total time in the EHR (EHR-Time8), time in the EHR outside scheduled hours, work outside of work (WOW8), and time spent on inbox (IB-Time8) were calculated. We examined the relationship between CTCC, EHR use metrics, and burnout using descriptive statistics and adjusted logistic regression models. Results We included data from 305 attendings, encompassing 242 432 ambulatory encounters (2021). Among them, 42% (128 physicians) experienced burnout. The median CTCC for all clinicians was 32.5 h. Unadjusted analyses revealed significant associations between CTCC, WOW8, IB-Time8, and burnout. In a final adjusted model, only CTCC remained statistically significant with an odds ratio estimate of 1.42 (95% CI, 1.00-2.01). Discussion These results suggest that CTCC is predictive of burnout and that purely measuring duration of interaction with the EHR itself is not sufficient to capture burnout. Conclusion Workload burden as manifested by average CTCC has the potential to be a practical, quantifiable measure that will allow for identification of clinicians at risk of burnout and to assess the success of interventions designed to address burnout. Lay Summary Electronic health records (EHRs) have been adopted widely to improve quality, safety, and efficiency. However, EHR use has also demonstrably contributed to clinician stress and burnout—which in turn may jeopardize patient safety and other outcomes the EHR proposes to improve. Effectively measuring burnout and understanding the drivers of burnout are critical to implementing programs to reduce burnout. Existing burnout assessment tools are burdensome to implement, and EHR use measures have limitations in predicting burnout. This study proposes a new metric, cumulated time to chart closure (CTCC), to address these gaps. CTCC measures the time elapsed from the start of a clinical visit to the completion of all required documentation, considering both EHR-based work and other demands on clinicians’ time—clinical, non-clinical work, and non-work responsibilities. The mismatch of these demands with the individual’s resources to address them is posited to result in burnout. In this study, 42% of 305 physicians from a large academic multi-specialty health system reported burnout. CTCC is significantly associated with burnout, while traditional EHR use measures are not. CTCC could serve as a valuable tool for more easily identifying physicians at risk of burnout and evaluating the impact of interventions to reduce burnout.